Effect of Romosozumab Treatment in Postmenopausal Women With Osteoporosis and Knee Osteoarthritis: Results From a Substudy of a Phase 3 Clinical Trial - Nancy E. Lane; Donald Betah; Cynthia Deignan; Mary Oates; Zhenxun Wang; Jen Timoshanko; Aliya A. Khan; Neil Binkley (ACR Open Rheumatology, 2024)
Objective Romosozumab is a bone‐forming agent approved for osteoporosis treatment. Here we report results of the protocol‐specified, noninferiority osteoarthritis substudy of the fracture study in postmenopausal women with osteoporosis (FRAME), which evaluated the effect of romosozumab versus placebo on knee osteoarthritis in patients with a clinical history of osteoarthritis. Methods Women in FRAME with a history of knee osteoarthritis were eligible for enrollment in the osteoarthritis substudy; key inclusion criteria were osteoarthritis‐related signal knee pain, morning stiffness lasting less than 30 minutes, knee crepitus, and knee osteoarthritis confirmed by x‐ray within 12 months. The protocol‐specified outcomes were change from baseline through month 12 in the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score, incidence of worsening knee osteoarthritis, and treatment‐emergent adverse events (TEAEs) with romosozumab versus placebo. In a post hoc analysis, percentage change from baseline to month 12 in bone mineral density (BMD) was assessed. Results Of 7180 women in FRAME, 347 participated in the osteoarthritis substudy (placebo, 177; romosozumab, 170). At month 12, no significant difference in progression of knee osteoarthritis was observed with romosozumab versus placebo (least squares mean total WOMAC score: –2.2 vs. –1.3; P = 0.71). Incidence of worsening symptoms of knee osteoarthritis was comparable between romosozumab (17.1%) and placebo (20.5%) (odds ratio 0.9 [95% confidence interval: 0.5, 1.7]; P = 0.69). Incidence of TEAEs of osteoarthritis was numerically lower with romosozumab (13 [7.7%]) versus placebo (21 [12.0%]). BMD gains were higher with romosozumab. Conclusion Romosozumab treatment did not impact knee pain or function in postmenopausal women with osteoporosis and knee osteoarthritis and resulted in significant BMD gains in these women.